2008
DOI: 10.1159/000153100
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Circumstances of Neonatal Deaths in 108 Consecutive Cases over a 10-Year Period at the Children’s Hospital of Lucerne, Switzerland

Abstract: Background: Neonatal deaths still represent the largest percentage of overall childhood mortality. Many deaths of neonates are preceded by end-of-life decisions; however, decision-making practices have been reported to vary widely from country to country. Objectives: To analyze principal causes and circumstances of all consecutive neonatal deaths at our institution over a 10-year period. Methods: All neonates who had died either in the delivery room (DR) or the neonatal intensive care unit (NICU) between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 38 publications
(28 reference statements)
2
59
2
Order By: Relevance
“…Reported neonatal (28-d) mortality fol-lowing NICU admission varies widely from 0.8% to 6.2% (Hack et al 2005;Wilkinson et al 2006;Berger and Hofer 2009;Ray et al 2012) although this number includes the gamut of diagnoses, including extreme prematurity and sepsis. Of 23,910 recorded infant deaths, 66% were in the neonatal period, of which the leading cause was congenital malformations, deformations, and chromosomal abnormalities (20.8%) .…”
Section: Impact and Incidence Of Monogenic Diseasesmentioning
confidence: 99%
“…Reported neonatal (28-d) mortality fol-lowing NICU admission varies widely from 0.8% to 6.2% (Hack et al 2005;Wilkinson et al 2006;Berger and Hofer 2009;Ray et al 2012) although this number includes the gamut of diagnoses, including extreme prematurity and sepsis. Of 23,910 recorded infant deaths, 66% were in the neonatal period, of which the leading cause was congenital malformations, deformations, and chromosomal abnormalities (20.8%) .…”
Section: Impact and Incidence Of Monogenic Diseasesmentioning
confidence: 99%
“…Our results are in contrast to other studies that found shorter time to death when withdrawal of care was applied. 6 We believe that this approach tended to be considered relatively late during hospitalization in our NICUs, that is, only when lifesupporting treatments were determined to be ineffective and death seemed imminent, resulting in prolonging life. 20,21 The increasing documentation ofparents' thoughts and requests with regard to their dying child demonstrates, in our opinion, the effects of the change in the medical teams'approach during the past decade, leading to open and clear discussions with parents while explaining all treatment options.…”
Section: Figurementioning
confidence: 99%
“…23,24 Active withdrawal of treatment is common in NICUs in Europe, and half of neonatal deaths occur with this approach in the United Kingdom, 25 France, 26 the Netherlands, 27 Switzerland, 6,28,29 and Germany. 9 In a multicenter survey 7 assessing physician's end-of-life decisions in NICUs across 7 European countries, physicians from all these countries were found to have "set limits to intensive interventions," including continuation of current treatment without escalation, withholding of emergency treatment, and withholding of intensive treatment (the latter with the exception of Italy).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The decision-making is preceded by discussions between the medical staff and parents to reach appropriate end-of-life answers for each infant 12,[15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%